Formation of the Institutional Model of Public Administration of Post-Industrial Transformation of the Ukrainian Industrial Complex - Dykan, Volodymyr; Tokmakova, Iryna; Kalicheva, Natalia; Korin, Myroslava; Kozlova, Anastasiia (International Journal of Engineering and Technology, 2018)
The analysis of the institutional factors that negatively influenced the activities of the industrial complex of Ukraine in the process of formation of the neo-liberal economy model was performed. It was clarified that the accelerated liberalization of economic relations in Ukraine caused the loss of the core function in ensuring the effective functioning of the industrial sector - management. On the basis of the study of the change of key economic development indicators, the consequences of the crisis in industry were found out. The current conditions of the Ukrainian industrial sector development were described by clarifying such trends as globalization, socialization and humanization, intellectualization and business integration. The conceptual provisions of the institutional model of public administration of the development of the Ukrainian industry on the basis of the post-industrial economy have been formed. The goals, objectives, strategic priorities of the industrial sector development were identified and the promising form of business organization for introduction of high-tech production was determined. The main areas for improving the public administration frame with respect to the regulatory, supporting and coordination components and by forming an effective mechanism of public control were clarified.Â Â